Belolična čigra Chlidonias hybrida - Šere, Dare (Acrocephalus, 1990)
At Lake Cerknica: one on 10th May 1990, 24 on 13th May 1990
Keywords: belolična čigra; Birds; Cerkniško jezero; Ornithology; ornitologija; ptiči; Slovenia; Slovenija